The Molecular Chaperone GRP78/BiP in the Development of Chemoresistance: Mechanism and Possible Treatment - Roller, Corinna; Maddalo, Danilo (Frontiers in Pharmacology, 2013)
Treatment of several types of cancer such as lung, breast, prostate and pancreas has shown notable progresses in the past decades. However, after an initial response, tumors eventually became resistant to chemotherapy. This phenomenon, known as chemoresistance, accounts for the death of most cancer patients. Several studies in patients refractory to therapy have revealed the upregulation of the molecular chaperone GRP78/BiP both at the RNA and protein expression level. Furthermore GRP78/BiP relocates to the cell membrane in malignant but not in benign cells. In this communication we review studies on the role and the mechanism of action of GRP78/BiP during development of chemoresistance in cancer cells. In addition we discuss the possible role of GRP78 as a biomarker and as a target in cancer therapy.